2020
DOI: 10.1136/thoraxjnl-2019-214360
|View full text |Cite
|
Sign up to set email alerts
|

Use of oscillatory positive expiratory pressure (OPEP) devices to augment sputum clearance in COPD: a systematic review and meta-analysis

Abstract: IntroductionOscillating positive expiratory pressure (OPEP) devices are intended to facilitate sputum clearance in chronic obstructive pulmonary disease (COPD), but there is uncertainty as to their place in treatment pathways. We aimed to review the existing literature to establish the evidence base for their use.MethodsA systematic search of records up to March 2020 was performed on PubMed, CINAHL, Medline (Ovid), Cochrane and Embase to retrieve clinical trials that evaluated the efficacy of OPEP devices in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…It is notable that although mucolytic therapies are widely prescribed, adjuncts to assist sputum clearance such as oscillatory positive expiratory pressure (OPEP) are much less commonly prescribed 52 . The evidence base to support the latter remains strikingly limited, given how common productive cough is in COPD 53 …”
Section: Addressing the Burden Of Copdmentioning
confidence: 99%
“…It is notable that although mucolytic therapies are widely prescribed, adjuncts to assist sputum clearance such as oscillatory positive expiratory pressure (OPEP) are much less commonly prescribed 52 . The evidence base to support the latter remains strikingly limited, given how common productive cough is in COPD 53 …”
Section: Addressing the Burden Of Copdmentioning
confidence: 99%
“…Current systematic reviews provide a comprehensive description and summary of the acceptance and dropout rates of different forms of TH interventions for patients with COPD. Generally, TH interventions are acceptable among the COPD population [ 11 , 20 , 23 , 24 , 67 , 68 , 74 , 75 ]. Nevertheless, methodological queries remain regarding the design of a more acceptable and feasible TH intervention, the best strategy to provide TH interventions (individual vs. community), components of TH interventions (solo vs. joint other treatments), technological aspects (classic vs. advanced), and COPD phenotypes (stable vs. non-stable) that will obtain more benefits from TH interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized results in this review focused on the key outcomes of interest, including the acceptance and dropout rates, reasons for dropout, and the possible factors that might impact acceptance and dropout rates. The overall acceptance rate in this paper refers to the number of participants who consented to participate divided by the number of participants who were approached to participate in the trial [ 23 , 24 ], and dropout rate refers to the total number of participants in each treatment arm who dropped out from the clinical trial divided by the total number of the participants who consented to participate in the clinical trial [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Burudpakdee et al [ 39 ] reported that use of the Aerobika OPEP device (Trudell Medical, Ontario, Canada) reduced exacerbations by 30% compared to no PEP/OPEP after an inpatient stay in a sample of 405 patients, while Tse et al [ 9 ] found that the use of OPEP significantly reduced all cause inpatient admissions at 12 month follow up in a retrospective study of 2476 patients. A recent systematic review of the use of OPEP to augment sputum clearance in COPD by Alghadmi et al [ 40 ] found that while OPEP devices can have a positive impact in COPD, confidence in the effect size is low, and the quality of evidence was low to moderate grade overall.…”
Section: Discussionmentioning
confidence: 99%